Sketching, product design, presentation - Eissen, Koos, ....-; Steur, Roselien, ....- (Amsterdam : BIS Publishers, 2014)
We are very pleased to announce the third book by our bestselling writers Koos Eissen and Roselien Steur. After the worldwide success of Sketching and Sketching: The Basics, the authors now shift their focus from 'how to sketch' to 'why you sketch'. For designers, sketching is a daily activity that can serve many goals. You can sketch to brainstorm, to find and articulate ideas or to present a project to other designers in your team or people from other departments. And of course you sketch to present projects to clients and production companies. All these goals require different sketching techniques, which will be even more effective if you understand how people view your sketches and how you can use your sketches to improve your way of communicating what you want. * New book by authors of Sketching * From how-to-sketch to why-to-sketch * Destined to become the # 1 go-to book on sketching presentation.
Keywords: Product design